Pentingnya Perilaku Konsumen Dan Strategi Pemasaran Bisnis Di Era Digital - Maharani, Riscia; Muhammad Arfan; Nur Herlina; Irfa Yanpetra; Muhammad Faqih Nurizal; Muhammad Ershanda; Djoko Hananto (PT. Kreasi Karya Majakata, 2024)
In the ever-growing digital era, the role of consumer behavior and marketing strategy in business becomes crucial. This article explains the importance of a deep understanding of consumer behavior in a digital context and the urgency of developing adaptive marketing strategies. Dynamic changes in technology have changed the way consumers interact with products and brands. Therefore, the emphasis on implementing marketing strategies that are responsive to these changes is the main focus. This article analyzes the key role of consumer behavior in shaping effective marketing strategies in the digital era, highlighting the importance of adaptability and innovation in achieving business success. Keywords: Consumer Behavior, Strategy and Digital Era